Virtual reality adoption during the COVID-19 pandemic: A uses and gratifications perspective. (December 2021) - Ball, Christopher; Huang, Kuo-Ting; Francis, Jess
Highlights: UGT is applied to examine the use and adoption of VR devices during the pandemic. Buying VR during the pandemic is related to use for work, education, and gaming. Games and entertainment are the most popular uses of VR during the pandemic. VR for telemedicine is the least popular use for VR during the COVID-19 pandemic. Social interactivity predicts the use and purchase intentions of VR devices. Social interactivity and use intentions serve as mediators of purchase intentions. Abstract: The coronavirus disease 2019 (COVID-19) pandemic has impacted all aspects of people's lives, including how we work, play, learn, exercise, and socialize. Virtual reality (VR) technology has the potential to mitigate many of the challenges brought about by the pandemic, which has spurred increased adoption. However, relatively low adoption overall and limited software still restrict the power of VR to address COVID-19 difficulties effectively. This study examines how the perceived impacts of COVID-19 might lead to different VR uses and gratifications and device ownership / variability. Furthermore, we investigate the importance of social interactivity within VR for increasing adoption intentions. We surveyed 298 Amazon Mechanical Turk users during the Fall of 2020. Results indicate that the pandemic's perceived impacts influenced the likelihood of acquiring VR for education, tourism, and work. For VR ownership and variability, those who purchased VR during the pandemic were more likely to report buying it for work. Those with access to high-end VR hardware were more likely to report a broader range of uses, including socializing, health, and telemedicine. Validating the importance of various applications during the pandemic, we found that the desire for social interactivity mediates the impacts of COVID-19 on future adoption intentions. Theoretically, we propose several gratifications sought via the use of VR during the pandemic. Practically, we discuss recommendations for future VR research, marketing, and software design.